Juridical analysis of abandoned shares in the process of changing the status of a public company to a private company - Herry Wahyu Andradjadi; Erniyanti Erniyanti; Markus Gunawan (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the legal framework, practical implementation, challenges, and possible solutions related to stranded shares in the process of converting a public limited liability company (PT) into a private PT (go private). Methodology: A normative juridical approach was applied by examining relevant legal instruments, including the Company Law, Capital Market Law, and OJK regulations. An empirical juridical approach was also employed through interviews with notaries, OJK officials, capital market practitioners, and case studies of issuers facing obstacles due to stranded shares. Results: The findings indicate that the absence of specific regulations regarding the classification and settlement of stranded shares significantly hampers the achievement of the General Meeting of Shareholders (GMS) quorum and obstructs the effectiveness of tender offers. Consequently, this condition delays the going private process and causes harm to active shareholders. Conclusion: Legal uncertainty resulting from unregulated stranded shares undermines corporate restructuring in the capital market. A comprehensive regulatory revision and enforcement mechanism are needed to address the issue effectively. Limitation: This research focuses on stranded shares in Indonesia’s capital market and does not provide comparative perspectives from other jurisdictions, which may offer alternative mechanisms. Contribution: This study enriches academic discourse and provides policy recommendations by highlighting the need for regulatory reform, the establishment of judicial remedies to exclude inactive shares, and investor education. It contributes to strengthening legal certainty and stakeholder protection in corporate governance.